Registration of 'Stingray CL+' soft white winter wheat. Issue 1 (9th December 2020) - Carter, A. H.; Balow, K. A.; Shelton, G. B.; Burke, A. B.; Hagemeyer, K. E.; Stowe, A.; Worapong, J.; Higginbotham, R. W.; Chen, X. M.; Engle, D. A.; Murray, T. D.; Morris, C. F.
Abstract: Soft white winter (SWW) wheat ( Triticum aestivum L.) cultivars with the Clearfield Production System technology are an important tool for producers in wheat production regions of Washington State. Paired with the use of the group 2 (Amino Acid Inhibitors/ALS) Beyond (BASF Corporation) herbicide (imazamox), tolerant wheat allows producers options where the current herbicide chemistry has not been adequate to control grass weeds. The objective of this research was to develop a two‐gene Beyond‐tolerant SWW wheat cultivar with improved resistance to the stripe rust pathogen and strawbreaker foot rot, maintains high yield potential across production regions, and has improved end‐use quality. 'Stingray CL+' (Reg. no. CV‐1171, PI 691557) SWW wheat was developed and released in March 2019 by the Agricultural Research Center of Washington State University. Stingray CL+ was tested under the experimental designations MAS100095‐2‐1‐S10‐1 and WA8275 CL+, assigned through progressive generations of advancement. Stingray CL+ is a two‐gene Beyond‐tolerant semi‐dwarf cultivar adapted for the high rainfall wheat production regions of Washington. Stingray CL+ has high‐temperature adult‐plant resistance to the stripe rust pathogen, is heterogeneous for the Pch1 gene for strawbreaker foot rot, is tolerant to the chemistry of Beyond herbicide, is intermediate in height, has midseason maturity, and has high grain volume weight and grain yield. The end‐use quality properties of Stingray CL+ are acceptable to meet both domestic and export market standards. Core Ideas: Stingray CL+ is a soft white winter wheat cultivar with herbicide tolerance developed for Washington. Stingray CL+ combines herbicide tolerance and disease resistance using marker‐assisted selection in wheat. Wheat productivity is improved through development of new wheat cultivars.